2009
DOI: 10.1002/jrs.2526
|View full text |Cite
|
Sign up to set email alerts
|

Phonon properties of nanosized bismuth layered ferroelectric material—Bi2WO6

Abstract: Nanosized Bi 2 WO 6 was synthesized by a mild hydrothermal crystallization process. This method allowed obtaining plate-like crystallites of very small thickness (down to 3 nm). The effect of particle size on the structure and properties of Bi 2 WO 6 was studied by X-ray diffraction (XRD), transmission electron microscopy, and Raman and infrared spectroscopies. It has been shown that the orthorhombic distortion decreases with decreasing particle size, but the structure of the smallest crystallites is still ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 35 publications
11
60
0
Order By: Relevance
“…Many properties of nanoparticles, such as surface and interface effects, 1 quantum size effect, 2 photocatalytic properties, 3 and phonon properties, 4 have been investigated. In humans, environmental exposure to nano-ZnO has shown that it stayed in the stratum corneum and accumulated in skin folds and/or hair follicle roots of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Many properties of nanoparticles, such as surface and interface effects, 1 quantum size effect, 2 photocatalytic properties, 3 and phonon properties, 4 have been investigated. In humans, environmental exposure to nano-ZnO has shown that it stayed in the stratum corneum and accumulated in skin folds and/or hair follicle roots of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Since the single crystal BWO had the polar axis perpendicular to the c-axis, it inferred the large remnant polarization of the BWO1 film is due to the highly a-oriented crystal structure of the BWO1 film. 15,16 Figure 3 To analyze the difference in the switching time, we evaluated ferroelectric domain wall energies of the two BWO thin films by Landau, Lifshitz, and Kittel's (LLK) scaling law. In the LLK law, the scaling exponent γ is proportional to the domain wall energy.…”
Section: Resultsmentioning
confidence: 99%
“…Since BWO films have a polar axis perpendicular to the c-axis, the highly a-oriented BWO2 film has a domain wall energy that is lower than the BWO1 film. 15,16 It is suggested that the BWO2 film has the fast polarization switching characteristics resulting from the low domain wall energy of the BWO thin films.…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…The FT-IR spectra of P1, P2, and P3 are given in Fig. 5a [32]. The bands observed at 1381 cm -1 infer to the bending vibrations of N-O bands [33,34].…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 99%